HUBUNGAN ANTARA KEAKTIFAN IBU DALAM KEGIATAN POSYANDU DENGAN STATUS GIZI BALITA - Aries Abiyoga (ITKES Wiyata Husada Samarinda, 2019)
The purpose of this study was to determine the correlation between the mother’s liveliness in Posyandu activities with the toddler nutritional status. This study was analytical survey with cross sectional design. The samples of this study were 38 samples with accidental sampling technique. The result of the study was kolmogorov alternative test obtained liveliness with nutrient status that significant p value 0,000 (<0,05) which mean that H0 was rejected and Ha was accepted. Mother activity in Posyandu activities is very important, mother's insight on how to overcome health problems and nutritional status of Toddler will be wider, because in Posyandu activities the Posyandu cadres will share their knowledge and experience on how to overcome the health mother’s problems, and infants and toddler, while the benefits the activity of Toddlers to Posyandu is the nutritional status of Toddlers can be monitored early so as to prevent the occurrence of nutritional problems in Toddlers, because Toddler is an important period in the process of growth and development (golden age). The conclusion in this study, there was significant correlation between correlation between the mother’s liveliness in Posyandu activities with the toddler nutritional status. It is suggested to mother of toddler to actively participate in Posyandu activity and to seek information about nutrition problem that happened to Toddler.